2020
DOI: 10.12785/jifs/050102
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Enterprise Risk Management Practices in Organizations: An Empirical Analysis of Takaful Industry Financial Performance

Abstract: In the E&Y global report on Takaful industry, it has been observed consecutively that an ineffective Enterprise Risk Management (ERM) is among the top five business risks of the Takaful Industry. The present study has been conducted with an aim to find the impact of Enterprise Risk Management (ERM) Implementation on the Financial Performance of the world Takaful Industry. In this regard, ERM implementation level has been measured through the availability of Chief Risk Officer (CRO), Establishment of a Risk Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Shad et al (2019) discovered that implementing an effective ERM through internal factors has a considerable positive impact on a company's overall performance. Furthermore, Omar and Javaria (2019) assessed the impact of ERM implementation on the worldwide Takaful Industry's financial performance using a sample of thirty Takaful Companies from 2012 to 2015 in (Saudi Arabia, the UAE, Bahrain, Bangladesh, Kuwait, Qatar, Malaysia, Pakistan, Sri Lanka, and Oman). They evaluated the ERM implementation based on internal and external factors, structure, and governance, and discovered that the ERM implementation had a positive impact on the Takaful Industry's financial performance.…”
Section: Internal Factors and Financial Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Shad et al (2019) discovered that implementing an effective ERM through internal factors has a considerable positive impact on a company's overall performance. Furthermore, Omar and Javaria (2019) assessed the impact of ERM implementation on the worldwide Takaful Industry's financial performance using a sample of thirty Takaful Companies from 2012 to 2015 in (Saudi Arabia, the UAE, Bahrain, Bangladesh, Kuwait, Qatar, Malaysia, Pakistan, Sri Lanka, and Oman). They evaluated the ERM implementation based on internal and external factors, structure, and governance, and discovered that the ERM implementation had a positive impact on the Takaful Industry's financial performance.…”
Section: Internal Factors and Financial Performancementioning
confidence: 99%
“…They evaluated the ERM implementation based on internal and external factors, structure, and governance, and discovered that the ERM implementation had a positive impact on the Takaful Industry's financial performance. Furthermore, certain empirical research has demonstrated that internal factors like ERM practise drivers have a favourable and considerable influence on firms' financial performance (e.g., Shad et al, 2019;Omar & Javaria, 2019;Malik et al, 2020;Saeidi et al, 2021;Yudianto et al, 2021;Jean-Jules & Vicente, 2021). According to the Agency Theory, putting in place a robust risk management system with elements like ERM dimensions ("internal factors, external factors, structure, and process") could boost overall business performance and shareholder value (Omar & Javaria, 2019;Setapa et al, 2020;Saeidi et al, 2021;Yudianto et al, 2021;Jean-Jules & Vicente, 2021).…”
Section: Internal Factors and Financial Performancementioning
confidence: 99%
See 2 more Smart Citations
“…As reported by, , in their study that all interest-free banks have greater or excess liquidity. In addition, Hamid and Azmi (2011), argues that in the absence of local capital market the interest-free banks were suffering from investing in liquidity projects, all their idle funds (Masood & Kiran, 2019). As the interest-free and interest-based banks are operating at different principles.…”
Section: Section 1: Islamic Banking Sector and Current Situation Of Pakistan Islamic Banks Difference Between Interest Based And Interestmentioning
confidence: 99%